Analisis Return On Investment (ROI) Dan Residual Income (RI) Guna Menilai Kinerja Keuangan PT Indocement Tunggal Prakarsa Tbk Periode 2010-2019 - Irsan; Masnoni; Hilwa Anggraini; Roy Saleh; Deka Tamara Ramadona (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This research is a quantitative descriptive study, namely research that aims to explain existing phenomena by using numbers to reserve individual or group characteristics. The result of this research is that the Return On Investment (ROI) and Residual Income (RI) of PT Indocement Tunggal Prakarsa Tbk, experienced a fairly good condition in the growth of its Return On Investment (ROI) and Residual Income (RI). The Return On Investment (ROI) value generated by the company is positive during the 2010-2019 period and the percentage experiences fluctuating conditions. Suggestions submitted by researchers to Through the results of calculations made regarding the company's financial performance, the company is expected to be more effective and efficient in using company assets, besides that the company is also expected to be able to stabilize the efficient cost of capital. So that the company can be optimal in achieving maximum profit. In carrying out financial performance, companies are expected to include elements of the cost of capital by using the Residual Income (RI) method.